Guidelines for Intraoperative Care in Cesarean Delivery: Enhanced Recovery After Surgery Society Recommendations (Part 2). Issue 3 (September 2019) - Caughey, A.B.; Wood, S.L.; Macones, G.A.; Wrench, I.J.; Huang, J.; Norman, M.; Pettersson, K.; Fawcett, W.J.; Shalabi, M.M.; Metcalfe, A.; Gramlich, L.; Nelson, G.; et al.
Abstract : ( Am J Obstet Gynecol . 2018;219:533–544) This is the second document in a series of 3 focused on the Enhanced Recovery After Surgery (ERAS) care program, specifically in regards to cesarean delivery (CD) and its intraoperative care. ERAS has both clinical benefits (decreased length of stay, complications, and readmissions) and decreased cost of care. This special report focused on the period beginning 30 to 60 minutes before the start of the procedure (decision to operate) and ending at hospital discharge. The ERAS CD program provides audit and feedback cycles for both scheduled and unscheduled CD, and creates recommendations based on clinical evidence that allow physicians to learn, modify, and improve their care processes, leading to improved patient health outcomes.